Formation of bioactive coatings by radio frequency magnetron sputtering using various calcium phosphate targets and working gases; Journal of Physics: Conference Series; Vol. 1281 : 14th InternationalConference on Films and Coatings (ICFC14) - Fedotkin A. Yu. Aleksandr Yurjevich (2019, 2019)
Title screen